Safety and efficacy of liraglutide 1.2mg in patients with mild and moderate renal impairment: the ABCD nationwide liraglutide audit. (11th March 2013) - Thong, KY; Walton, C; Ryder, REJ; ,
Abstract: Liraglutide is not predominantly eliminated by renal excretion. We assessed its safety and efficacy among patients with mild and moderate renal impairment. Patients from a nationwide audit of liraglutide (1.2mg) use were divided according to pre‐treatment renal function calculated by the Cockcroft‐Gault formula. Adverse events, liraglutide discontinuation and changes in HbA1c, weight, systolic blood pressure and serum creatinine were compared between groups of different pre‐treatment renal function. As compared with patients with normal renal function (n=1446), patients with mild renal impairment (n=288) and moderate renal impairment (n=57) were equally likely to report gastrointestinal side effects (adjusted OR 1.11 [95% CI 0.80–1.54] and 0.67 [95% CI 0.31–1.48]), respectively, but more frequently stopped liraglutide due to gastrointestinal side effects (adjusted OR 2.32 [95% CI 1.45–3.74] and 2.37 [95% CI 0.97–5.81]), respectively. Minor hypoglycaemia and acute renal failure were uncommonly reported and were not more frequent among patients with renal impairment. Patients remaining on treatment in all three groups achieved significant HbA1c and weight reduction at six months (between 11 to 12mmol/mol [1.0 to 1.1%] and ‐3.6 to ‐3.8kg). No effect of renal function was seen influencing the degree of HbA1c and weight reduction. Liraglutide treatment was associated with a small reduction in serum creatinine among patients with renal impairment. We concluded that liraglutide was safe, efficacious but more frequently discontinued among patients with mild renal impairment. More data are needed to establish its safety among patients with moderate or more significant renal impairment. Copyright © 2013 John Wiley & Sons.